Stress analysis in mandibular molars restored with cast and pre-fabricated post-and-cores using finite element technique - Mojtaba Mahmoodi; Ali Reza Saeidi; Sayed Abdolreza Ganjalikhan Nasab; Maryam sadat Hashemipour (مجله دانشکده دندانپزشکی اصفهان, 2011)
Introduction: The main factor involved in the failure of endodontically treated teeth is crown reconstruction rather than root canal treatment itself. The present study compared stress distribution in pre-fabricated and cast post-and-cores by finite element analysis. In addition, the effect of post material was evaluated. Method and materials: In this cross-sectional descriptive-analytical study, an extracted sound human mandibular second molar was embedded in an acrylic resin cylindrical mold. Axial cross-sections were prepared by abrasion and photographed; the images were transferred into a computer software program and a three-dimensional solid model of the tooth was prepared. A load of 10.43 MPa was applied on a 23-mm2 surface area of the occlusal surface at an angle of 45°. Finally, different restoration models for pre-fabricated and cast posts were designed and the effect of post material was analyzed.Results: Cast posts generated less stresses compared to pre-fabricated posts; however, pre-fabricated posts were more conservative form the stress location viewpoint. Regarding stress concentration, gold posts were more favorable in comparison to titanium posts because stress concentration in gold posts takes place in the cervical region, so that if root failure occurs, reconstruction is possible. Conclusion: Cast posts result in less stress in roots compared to pre-fabricated posts. Except for gold cast posts, all other cast posts are more dangerous in relation to stress distribution. Key words: Dental stress analysis, Finite element analysis, Post-core, Technique.